Sclerosing Mesenteritis Presenting with Small Bowel Obstruction in a Patient with Compensated Cirrhosis: A Case Report - Zacharioudakis, Georgios; Liava, Christina; Andronikou, Apostolos; Syndouka, Eleni; Kambaroudis, Apostolos; Akriviadis, Evangelos (Archives of Clinical and Medical Case Reports, 2021)
Sclerosing Mesenteritis (SM) is a rare fibroinflammatory disease of unknown etiology in which intestinal obstruction results from encasement of variable lengths of bowel by a dense fibrocollagenous membrane that gives the appearance of a cocoon. To our knowledge no cases of SM have been reported in patients with compensated cirrhosis without ascites. We report a case with SM diagnosed at laparotomy due to rapidly worsening small bowel obstruction, in a patient with compensated alcoholic cirrhosis. A 50-yearsold Caucasian male was evaluated because of cramping abdominal pain and discomfort associated with diarrhea, occasional post-prandial vomiting, fatigue and a significant weight loss. Compensated alcoholic cirrhosis had been diagnosed, two months before current presentation. Physical examination revealed abdominal distention with highpitched metallic sounds and bilateral peripheral pedal edema. Computed tomography of the abdomen demonstrated severe dilated small bowel loops as well as fluid into the peritoneal cavity. Based on the imaging findings, a surgical procedure was carried out. During laparotomy, an extra fibrous layer fully surrounding the small intestine was divided and a side-to-side functional ileo-cecum anastomosis was performed. Histopathological examination revealed fibroconnective tissue proliferation and inflammatory infiltration. Combined with the characteristic surgical findings a diagnosis of SM was made in a patient with compensated alcoholic cirrhosis. The patient recovered uneventfully and at 6-month follow-up he had no symptoms or signs of SM recurrence. The insidious onset of bowel obstruction symptoms in patients with even compensated cirrhosis, should include SM in the differential diagnosis.